2017
DOI: 10.18632/oncotarget.18843
|View full text |Cite
|
Sign up to set email alerts
|

Arginine auxotrophic gene signature in paediatric sarcomas and brain tumours provides a viable target for arginine depletion therapies

Abstract: Paediatric sarcomas and brain tumours, remain cancers of significant unmet need, with a poor prognosis for patients with high risk disease or those who relapse, and significant morbidities from treatment for those that survive using standard treatment approaches. Novel treatment strategies, based on the underlying tumour biology, are needed to improve outcomes. Arginine is a semi-essential amino acid that is imported from the extracellular microenvironment or recycled from intracellular precursors through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…A reduced transcription level of one of those genes was seen in particular in cells with normal ASS1/ASL expression [31]. Supporting these findings, a recent report described significant downregulation of OTC in pediatric sarcomas and brain tumors with normal ASS1 expression [32].…”
Section: Arginine Auxotrophy In Human Malignanciessupporting
confidence: 52%
“…A reduced transcription level of one of those genes was seen in particular in cells with normal ASS1/ASL expression [31]. Supporting these findings, a recent report described significant downregulation of OTC in pediatric sarcomas and brain tumors with normal ASS1 expression [32].…”
Section: Arginine Auxotrophy In Human Malignanciessupporting
confidence: 52%
“…[4][5][6][7] Peripheral blood arginine concentrations are lower than healthy controls in AML, neuroblastoma, and pediatric cancer patients at diagnosis (Figure 1A-C) and Arginase I is expressed within the tumor microenvironments of adult tumor subtypes (supplemental Figure 1A-B, available on the Blood Web site). 8 T cells are acutely sensitive to extracellular concentrations of arginine because they have low/ absent expression of the arginine resynthesis pathway enzymes ASS and OTC (supplemental Figures 1C and 2A). [9][10][11][12] We hypothesized that insertion of ASS and/or OTC enzymes would allow CAR-T cells to refuel themselves, in a low arginine microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…In hepatocellular carcinoma, reduced expression of CPS1 is linked to hypermethylation of the promoter and is related to reduced survival and lymphatic invasion [ 66 ]. A recent study reported decreased OTC expression in HCC patients’ samples; OTC is one of the characteristic arginine metabolism genes in pediatric sarcomas, brain tumors, and acute lymphoblastic leukemia [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%